BIOEKOLOGI IKAN SILUK IRIAN (Scleropages jardinii) DIKABUPATEN MERAUKE PROVINSI PAPUA - Haryono, Haryono; Tjakrawidjaja, Agus Hadiat (BERITA BIOLOGI, 2003)
Study on bio-ecological aspect of bony tongue (Scleropages jardinii) was done in Merauke, Papua Province on May 1997.The aims of this study are to know the aspects of reproduction, behavior, habitat, and conservation. The results recorded fecundity between 87 -161 eggs, fertility 45-84. This fish is a predator and carnivorous. Water quality is suitable for fish life as well as their reproduction. Conservation action is urgently important.